Nursing managers' strategies for reducing interpersonal and interprofessional conflicts in the Covid-19 Pandemic - Krisna Yetti Malawat; Rr.Tutik Sri Hariyati; Kartika Mawar Sari (Alta Dharma Publisher, 2020)
The COVID-19 pandemic is a challenge for all parties and needs a fast, precise and integrated response. Nurses as the frontline are the people most at risk of contracting this disease. Changes in all aspects require that nurses can collaborate with other interprofessional teams and makes nurses vulnerable to pressure and stress that can lead to conflict. The role of nursing managers in creating a conducive work atmosphere and preventing interprofessional conflicts is needed. This study used literature reviews through the ScienceDirect online database, SAGE journals, Wiley Online Library and other sources, which aims to analyze the strategy of nurse managers in preventing interprofessional conflicts in the era of the COVID-19 pandemic. The results show that providing education on the control and prevention of COVID-19 infection, supervision, improving effective communication through information technology, optimizing workflows, improving nursing standards, providing support and implementing crisis management are strategies that can be used by nurse managers. Assertiveness can be used as conflict management to prevent interprofessional conflicts in the pandemic era. Each profession can communicate positively with other interprofessional teams, accept each other and carry out professional responsibility and making decisions about COVID-19 patients.